Thin alkali metal composite foil, preparation method thereof and application of thin alkali metal composite foil in secondary battery electrode
By placing the metal indium foil between the metal sodium foil, a composite foil with Na|In|Na structure is formed, and thinned through mechanical rolling and half-folding operations, the problems of material composition distortion and equipment requirements in traditional preparation technology are solved, and the preparation and application of high-performance thin alkali metal composite foil is realized.
Patent Information
- Application Number
- CN202411967525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional thin alkali metal composite foil preparation technology has problems such as material composition distortion, decreased interface uniformity, and strict equipment requirements and difficulty in meeting the needs of large-scale production.
A composite foil with a Na|In|Na "sandwich" structure is formed by placing metal indium foil between two layers of metal sodium foils, and gradually thinning to a Na/Na-In(NNI) composite foil with a thickness of no more than 35 μm by mechanical rolling and folding operations.
It significantly improves the processability and stability of alkali metal foils, improves the electrochemical performance of sodium metal negative electrodes, and provides a new technical path for high-performance sodium metal battery electrodes.
Smart Images

Figure CN119725372A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary battery materials, and in particular relates to a thin alkali metal composite foil and a preparation method thereof and an application thereof in secondary battery electrodes. Background Art
[0002] In recent years, the rapid development of portable electronic devices, electric vehicles and large-scale energy storage systems has driven a sharp increase in demand for resource-rich, high-energy-density batteries. However, widely used lithium-ion batteries are limited by the limited reserves of lithium resources (the content in the earth's crust is only 0.0065%) and the uneven distribution of resources, resulting in high costs and difficulty in meeting the needs of sustainable development. In contrast, the content of sodium in the earth's crust is about 2.74%, it is widely distributed and has low cost, making it an alternative material for the next generation of high-energy-density batteries. Therefore, optimizing the utilization of lithium and sodium resources, reducing resource waste and improving the utilization rate of battery materials have become key issues in current research. The development of thin alkali metal composite foils provides a feasible technical path to meet this challenge.
[0003] Alkali metals (such as sodium and lithium) are the core negative electrode materials for high energy density batteries due to their high theoretical specific capacity and low electrochemical potential. Metallic sodium, with its low cost and high resource utilization, provides a key material basis for building low-cost, high specific energy sodium metal batteries. However, metallic sodium faces many challenges in practical applications, including unstable interface stability caused by high chemical activity, low yield strength limiting its machinability, and safety hazards caused by dendrite growth during cycling. Therefore, the development of thin alkali metal composite foils with excellent processing properties and stable electrochemical behavior is crucial to improving battery performance and reducing resource waste.
[0004] In the design of sodium metal full batteries, the areal capacity of the positive electrode / negative electrode (N / P) is usually limited to less than 2 to ensure the cycling stability of the battery. The areal capacity of common sodium battery positive electrode materials is about 2 mAh cm -2 , and 1mAh cm -2 The thickness of pure sodium foil is equivalent to 8.9μm. Therefore, to ensure that the battery has high practical value (i.e., N / P ratio <2), the thickness of sodium metal foil should be less than 35μm. In addition, in sodium-ion full batteries, the formation of the solid electrolyte interface (SEI) process irreversibly consumes sodium ions from the positive electrode, which directly reduces the energy density of the battery. Using thin sodium composite foil to compensate for sodium is a feasible technical path to address this challenge.
[0005] At present, conventional methods for preparing thin alkali metal composite foils include hot melting, thermal evaporation, and electrodeposition technologies. These methods have improved the controllability of foil thickness and interface bonding performance to a certain extent, but there are still many limitations. For example, hot melting and thermal evaporation technologies require a high temperature environment, which can easily lead to imbalance in material composition and decreased interface uniformity; electrodeposition technology has strict requirements on equipment and is difficult to meet the needs of large-scale production. The above problems significantly limit the practical application of traditional preparation technologies in high-performance alkali metal negative electrodes.
[0006] The present invention provides a thin alkali metal composite foil and a preparation method thereof, wherein a metal indium foil is placed between two layers of metal sodium foil to form a composite foil having a Na|In|Na "sandwich" structure, the Na|In|Na composite foil is mechanically rolled and folded in half, and the mechanical rolling and folding operations are repeated until a Na / Na-In (NNI) composite foil is prepared. The preparation method of the present invention can prepare a thin sodium metal composite foil having a thickness of no more than 35 μm, and significantly improves the processability and stability of the alkali metal foil. Summary of the invention
[0007] The purpose of the present invention is to provide a thin alkali metal composite foil and a preparation method thereof and an application in secondary battery electrodes, so as to solve the problems in the traditional thin alkali metal composite foil preparation technology proposed in the above background technology, that the hot melting and hot evaporation technologies are prone to cause material composition imbalance and decreased interface uniformity, and that the electrodeposition technology has strict equipment requirements and is difficult to meet the needs of large-scale production.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] The first aspect of the present invention provides a thin alkali metal composite foil, wherein the thin alkali metal composite foil uses metallic sodium as a matrix, and disperses a dopant, a product formed by a reaction between metallic sodium and the dopant, or a combination of two, in the matrix, wherein the matrix is in a foil shape and has a thickness of no more than 35 μm;
[0010] The dopant is selected from one or a combination of two or more of a metal element, a non-metal element, a carbon nanotube, a carbon nanorod or a carbon fiber.
[0011] Preferably, the dopant is metallic indium; the thin alkali metal composite foil comprises metallic sodium and a Na-In alloy phase, wherein the Na-In alloy phase is uniformly dispersed in metallic sodium; the Na-In alloy phase is an alloy formed by the reaction of metallic sodium and metallic indium; and the volume ratio A of the metallic sodium and metallic indium is 3<A≤9.
[0012] Preferably, the dopant is red phosphorus; the mass ratio of the red phosphorus to metallic sodium is 25-30:75-70.
[0013] The second aspect of the present invention provides a method for preparing the thin alkali metal composite foil, which is specifically as follows:
[0014] The dopant is placed between a number of metal sodium foils, the metal sodium foils are aligned and stacked, and the stacked metal sodium foils are processed by a folding-rolling method to obtain a thin alkali metal composite foil.
[0015] When the dopant is red phosphorus, the preparation method is as follows:
[0016] S1. In an argon atmosphere, red phosphorus powder is placed between two metal sodium foils. The two metal sodium foils are stacked and aligned and then mechanically rolled to form a composite foil as a whole;
[0017] S2. Repeatedly stacking and rolling the entire composite foil until a thin alkali metal composite foil with a thickness of no more than 35 μm is prepared.
[0018] Preferably, the two pieces of metallic sodium foil have the same shape and size.
[0019] The dopant is metallic indium, and the preparation method comprises the following steps:
[0020] S1. In an argon atmosphere, metal indium foil and metal sodium foil are alternately stacked to form a composite foil similar to Na|In|Na;
[0021] S2. Mechanically rolling and folding the Na|In|Na composite foil, repeating the mechanical rolling and folding operations to reduce the thickness of the Na|In|Na composite foil continuously. After the thickness of the Na|In|Na composite foil is less than 50 μm, the thickness gradually decreases in the range of 0<t<10 μm, until a Na / Na-In composite foil with a thickness of no more than 35 μm is prepared, that is, a thin alkali metal composite foil.
[0022] Preferably, the thickness t of the Na / Na-In composite foil is 1≤t≤35 μm.
[0023] Preferably, the volume ratio of the metal sodium foil to the metal indium foil is 6:1.
[0024] The third aspect of the present invention proposes the use of a thin alkali metal composite foil in a secondary battery electrode, wherein the secondary battery is a high specific energy sodium metal battery or a sodium ion battery.
[0025] Preferably, the thin alkali metal composite foil is used as the negative electrode.
[0026] Preferably, the thin alkali metal composite foil is used as the negative electrode sodium compensation material.
[0027] Preferably, the positive electrode of the secondary battery is one of a sodium-containing transition metal oxide, a polyanion compound and a Prussian blue / white compound.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention proposes a thin alkali metal composite foil and a preparation method thereof, which are suitable for the optimized design of sodium metal battery electrodes. Under normal temperature conditions, the present invention places a metal indium foil between two layers of metal sodium foil to form a composite foil with a Na|In|Na "sandwich" structure; through repeated mechanical rolling, the metal indium foil and the metal sodium foil are prompted to react at the interface to generate a Na-In alloy phase with a second phase reinforcement effect. Subsequently, through repeated folding and further rolling, the Na-In alloy phase is uniformly dispersed in the sodium metal matrix, thereby improving the hardness, strength and plasticity of the sodium metal, improving its mechanical processing performance, and successfully preparing a thin sodium metal composite foil with a thickness of no more than 35μm. At the same time, the Na-In alloy phase in the sodium metal matrix has high ionic conductivity and sodium affinity, which can effectively reduce the initial nucleation overpotential of sodium deposition, improve the sodium ion diffusion kinetics, and then improve the electrochemical performance of the sodium metal negative electrode, providing a new technical path for the development of high-performance sodium metal battery electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a real picture of pure Na pressed to 100 microns;
[0031] Figure 2 The XRD pattern of the NNI composite foil prepared under the condition that the volume ratio of Na foil to In foil is 6:1 in Example 1;
[0032] Figure 3 This is a cycle diagram of a full battery assembled with a NNI composite negative electrode and a sodium vanadium phosphate (NVP) positive electrode at a current density of 2C in Example 1;
[0033] Figure 4 This is a physical picture of the NNI composite foil prepared under the condition of a volume ratio of Na foil to In foil of 6:1 in Example 1;
[0034] Figure 5 This is a physical picture of the NNI composite foil prepared with a volume ratio of Na foil to In foil of 9:1 in Example 2;
[0035] Figure 6 This is a physical picture of the NNI composite foil prepared with a volume ratio of Na foil to In foil of 3:1 in Example 3;
[0036] Figure 7 The cycle diagram of the full battery assembled with the NNP (Na / Na3P) composite negative electrode and the NVP positive electrode at a current density of 0.5C in Example 5;
[0037] Figure 8 It is a comparison chart of the energy density and cycle performance of the full battery assembled with the NVP positive electrode after the P / C negative electrode is pre-sodiumized by the NNP composite foil in Example 5;
[0038] Fig. 9 This is a physical picture of the composite foil prepared from carbon nanotubes, metal indium foil and metal sodium foil in Example 6. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The present invention proposes a method for preparing a thin alkali metal composite foil. Due to its active chemical properties, low yield strength, high viscosity and strong deformation ability, it is difficult to process metallic sodium to a thickness of less than 50 μm by conventional rolling process. Figure 1 The figure shows a real picture of pure Na pressed to 100 μm, at which point the metal sodium foil breaks directly. The present invention proposes a Na|In|Na "sandwich" structure composite foil in which a metal indium foil is sandwiched between two layers of metal sodium foil, so as to enhance the mechanical processing properties of the composite foil by utilizing the regulating effect of the indium foil, and further study the effect of red phosphorus on the mechanical processing properties of the composite foil.
[0041] The preparation method using indium foil specifically includes the following steps:
[0042] Step 1: in an argon atmosphere, placing a metal indium foil on the surface of a first metal sodium foil and covering it with a second metal sodium foil to form a Na|In|Na composite foil;
[0043] Step 2: Mechanically roll and fold the Na|In|Na composite foil, and repeat the mechanical rolling and folding operations to reduce the thickness of the Na|In|Na composite foil. After the thickness of the Na|In|Na composite foil is less than 50 μm, the thickness gradually decreases in the range of 0<t<10 μm, until a Na / Na-In (NNI) composite foil with a thickness of no more than 35 μm is prepared, which is a thin alkali metal composite foil.
[0044] This embodiment uses metallic sodium as the matrix and utilizes the hardness and excellent ductility of metallic indium foil to prepare a composite foil. During the mechanical rolling process, the metallic indium foil improves the hardness and plasticity of metallic sodium, and reacts with metallic sodium at the interface to generate a Na-In alloy phase. The folding operation after rolling further embeds the generated Na-In alloy phase evenly into the sodium metal block. After multiple folding and rolling operations, the metallic indium foil reacts completely with metallic sodium, and the generated Na-In alloy phase is evenly dispersed in the sodium matrix, significantly improving the hardness, ductility and processability of metallic sodium, and finally successfully preparing a thin sodium metal composite foil with a thickness of no more than 35 μm.
[0045] Under preferred conditions, the thickness t of the Na / Na-In composite foil is 1≤t≤35 μm.
[0046] Under preferred conditions, the ratio of metal sodium foil to metal indium foil (based on the total volume of the sheet) is 4 to 9:1, more preferably 6:1. Metal indium reacts with metal sodium to form Na-In alloy, the content of which is directly determined by the ratio of indium foil to sodium foil, which significantly affects the mechanical processing properties and electrochemical behavior of the composite foil. When the ratio of indium foil to sodium foil is low, the content of Na-In alloy in the composite foil is insufficient. On the one hand, the machinability of metal sodium cannot be significantly improved, and it is difficult to prepare a thin alkali metal composite foil with a thickness of less than 50 μm; on the other hand, the number of nucleation sites and sodium ion transmission channels of Na-In alloy is reduced, which limits the improvement of the electrochemical performance of the negative electrode material. However, when the ratio of sodium foil to indium foil is too high (such as 3:1), the excess indium in the composite foil causes the elemental sodium to be completely reacted or less involved, resulting in the fragility of the composite foil during rolling, affecting its integrity. Under preferred conditions, the first metal sodium foil and the second metal sodium foil are the same size. This is beneficial to increase the contact area between the metal indium foil and the metal sodium foil during the rolling process, thereby producing a more uniform Na-In alloy layer and avoiding the uneven distribution of the Na-In alloy phase in the sodium metal matrix.
[0047] Under preferred conditions, all the above operations are carried out in an argon glove box.
[0048] The present invention will be described in detail below with reference to the embodiments and accompanying drawings.
[0049] Embodiment 1:
[0050] The method for preparing a thin alkali metal composite foil comprises the following steps:
[0051] Step 1: Cut out a first metal sodium foil and a second metal sodium foil in a regular rectangular or square shape, lay a metal indium foil of a corresponding size on the surface of the first metal sodium foil, and then cover the surface of the metal indium foil with the second metal sodium foil, so that the metal indium foil is completely attached to the first metal sodium foil and the second metal sodium foil to form a Na|In|Na composite foil;
[0052] Step 2: Place the Na|In|Na composite foil between the rollers of the roller machine, adjust the roller spacing and perform the rolling operation. By continuously reducing the roller spacing, the Na-In alloy continues to migrate, a sodium / indium interface appears and continues to react. After the composite foil is thinned to a certain thickness, a folding operation is performed, and the folded composite foil is then rolled to thin it. Repeat this operation so that the generated Na-In alloy is evenly distributed in the matrix of metallic sodium until a NNI composite electrode (composite foil) with a thickness of 30 μm is prepared.
[0053] In order to further explore the morphological characteristics of the obtained composite foil, the present invention adopts conventional X-ray diffraction (XRD) to characterize the obtained composite foil. Figure 2 This is the XRD pattern of NNI composite foil prepared under the condition of Na foil and In foil volume ratio of 6:1. Figure 3 This is the cycle diagram of the full battery assembled with NNI composite anode and sodium vanadium phosphate (NVP) cathode at 2C current density. Figure 4 This is a physical picture of the NNI composite foil prepared under the condition of a volume ratio of Na foil to In foil of 6:1; it can be seen that the thickness of the prepared NNI composite foil is 30μm.
[0054] Embodiment 2:
[0055] The method for preparing the thin alkali metal composite foil in Example 2 is different from that in Example 1 in that the ratio of the metal sodium foil to the metal indium foil is 9:1, until a NNI composite electrode with a thickness of 30 μm is prepared.
[0056] Figure 5 This is a photo of the NNI composite foil prepared with a volume ratio of Na foil to In foil of 9:1. It can be seen that the thickness of the NNI composite foil prepared at this volume ratio can still reach 30 μm.
[0057] Embodiment 3:
[0058] The method for preparing the thin alkali metal composite foil in Example 3 is different from that in Example 1 in that the ratio of the metal sodium foil to the metal indium foil is 3:1, and it is difficult to prepare an NNI composite electrode with a thickness of less than 35 μm.
[0059] The obtained composite foil was characterized by conventional electron photography, and the results are as follows.
[0060] Figure 6 The actual picture of the NNI composite foil prepared with a volume ratio of Na foil to In foil of 3:1. After the composite foil is repeatedly rolled and folded several times, the elemental sodium is completely converted into Na-In alloy or the residual amount is small. Obvious cracks and gaps have appeared on the composite foil of about 500μm, making it difficult to further thin it.
[0061] Embodiment 4:
[0062] The method for preparing the composite foil in this embodiment is different from that in Embodiment 1 in that tin foil is used to replace indium foil, wherein the ratio of sodium foil to tin foil is 6:1.
[0063] During the preparation process, the sodium-tin particles formed are relatively large and break when the rolling thickness reaches 50 μm, making it difficult to form a complete thin alkali metal composite film. Therefore, the metal single substance is preferably metal indium.
[0064] Embodiment 5:
[0065] The preparation method of the composite foil in Example 5 is different from that in Example 1 in that red phosphorus powder is used to replace the indium foil. The preparation method is as follows:
[0066] S1. In an argon atmosphere, placing red phosphorus powder on the surface of a first metal sodium foil, and then covering it with a second metal sodium foil to form a Na|P|Na composite foil;
[0067] S2. Mechanically rolling and folding the Na|P|Na composite foil, repeating the mechanical rolling and folding operations until a Na / Na3-P (NNP) composite foil having a thickness of no more than 35 μm is prepared.
[0068] In this embodiment, the mass fraction of red phosphorus is controlled at 25-30%. The high phosphorus content directly leads to an increase in the volume and mass ratio of Na3P in the composite foil, which is beneficial to reduce the volume change of the composite foil during the sodium deposition / dissolution process when the composite foil is used as a sodium metal negative electrode; and reduce the sodium precipitation problem caused by excessive sodium when used as a sodium compensation material. When the amount of red phosphorus introduced exceeds 30%, a whole composite foil cannot be formed.
[0069] Figure 3 This is the cycle diagram of the full battery assembled with the NNI composite negative electrode and the NVP positive electrode in Example 1 at a current density of 2C. Under the harsh condition of an N / P ratio of 1, the capacity retention rate of the battery is 96% after 27 cycles.
[0070] Figure 7 This is the cycle diagram of the full battery assembled with the NNP (Na / Na3P) composite negative electrode and the NVP positive electrode at a current density of 0.5C in this embodiment. When the N / P ratio is 1.85, the capacity retention rate of the battery after 100 cycles is 95%.
[0071] Figure 8 This is a comparison chart of the energy density and cycle performance of the full battery assembled with the NVP positive electrode after the NNP composite foil pre-sodiumized the P / C negative electrode in this embodiment. The initial charge is calculated based on the total mass of the electrode, and the energy density of the battery after pre-sodiumization is increased by 35%.
[0072] By comparison, it can be seen that since the product Na3P after NNP pre-sodiumization is the same as the product of P / C negative electrode sodiumization, NNP composite foil is the preferred material for P / C negative electrode sodium compensation.
[0073] Embodiment 6:
[0074] The method for preparing the composite foil in Example 6 is different from that in Example 1 in that carbon nanotubes are further added, and the carbon nanotubes and indium foil are placed between sodium foils together until a composite foil with a thickness of 20 μm is prepared.
[0075] Fig. 9 The actual picture of the composite foil prepared from carbon nanotubes, metal indium foil and metal sodium foil; it can be seen that the thickness of the prepared composite foil is 20μm, and the carbon nanotubes uniformly dispersed in the composite foil form a cross-linked structure, which supports the thickness of the composite foil to be thinner. Carbon nanorods and carbon fibers can play the same role.
[0076] Performance Test:
[0077] (1) Machining performance test:
[0078] The hardness, viscosity and tensile strength of the NNI composite foil prepared in Example 1 were tested, and the results were as follows:
[0079] The formation of Na-In alloy increases the hardness of metallic sodium, thereby improving the processability of NNI composite foil and making it less likely to cause surface tearing during rolling.
[0080] The formation of Na-In alloy effectively reduces the viscosity of metallic sodium, thereby reducing the adhesion between it and the roller, which is beneficial to the further thinning of the NNI composite foil.
[0081] The formation of Na-In alloy increases the tensile strength of metallic sodium, thereby improving the ductility and plasticity of the NNI composite foil.
[0082] (2) Electrochemical performance test:
[0083] The NNI composite electrode prepared in Example 1 and the pure sodium electrode were assembled into symmetrical batteries, and the performance of the symmetrical batteries was tested. The results were as follows:
[0084] Compared with the pure sodium electrode symmetric battery, the initial nucleation overpotential and overvoltage of the composite negative electrode symmetric battery are both reduced, indicating that the Na-In alloy phase in the composite negative electrode can effectively reduce the nucleation potential of sodium deposition, increase the diffusion rate of sodium ions, and improve the electrochemical performance of the battery.
[0085] The surface exchange current of the NNI composite electrode is higher than that of the pure sodium electrode, indicating that the presence of Na-In alloy helps to improve the diffusion kinetics of sodium ions on the electrode surface.
[0086] The above description is only used to help understand the method of the present invention and its core essence, but the protection scope of the present invention is not limited thereto. For those skilled in the art in the art, equivalent replacement or change according to the technical solution and inventive concept of the present invention within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A thin alkali metal composite foil, characterized in that: The thin alkali metal composite foil has metallic sodium as a matrix, in which a dopant, a product formed by the reaction of metallic sodium and the dopant, or a combination of two is dispersed, and the matrix is in a foil shape and has a thickness of no more than 35 μm; The dopant is selected from one or a combination of two or more of a metal element, a non-metal element, a carbon nanotube, a carbon nanorod or a carbon fiber.
2. The thin alkali metal composite foil according to claim 1, characterized in that: The dopant is metallic indium; the thin alkali metal composite foil comprises metallic sodium and a Na-In alloy phase, wherein the Na-In alloy phase is uniformly dispersed in the metallic sodium; the Na-In alloy phase is an alloy formed by the reaction of metallic sodium and metallic indium; and the volume ratio A of the metallic sodium and metallic indium is 3<A≤9.
3. The method for preparing the thin alkali metal composite foil according to claim 1, characterized in that: The details are as follows: placing the dopant between a number of metal sodium foils, aligning and stacking the metal sodium foils, and processing the stacked metal sodium foils by a folding-rolling method to obtain a thin alkali metal composite foil.
4. The method for preparing the thin alkali metal composite foil according to claim 3, characterized in that: The dopant is red phosphorus, and the preparation method is as follows: S1. In an argon atmosphere, red phosphorus powder is placed between two metal sodium foils, wherein the mass ratio of red phosphorus to metal sodium is 25-30:75-70; the two metal sodium foils are stacked and aligned, and then mechanically rolled to form a composite foil as a whole; S2. Repeatedly stacking and rolling the entire composite foil until a thin alkali metal composite foil with a thickness of no more than 35 μm is prepared.
5. The method for preparing the thin alkali metal composite foil according to claim 3, characterized in that: The dopant is metallic indium, and the preparation method comprises the following steps: S1. In an argon atmosphere, metal indium foil and metal sodium foil are alternately stacked to form a Na|In|Na composite foil; S2. Mechanically rolling and folding the Na|In|Na composite foil, repeating the mechanical rolling and folding operations to reduce the thickness of the Na|In|Na composite foil continuously. After the thickness of the Na|In|Na composite foil is less than 50 μm, the thickness gradually decreases in the range of 0<t<10 μm, until a Na / Na-In composite foil with a thickness of no more than 35 μm is prepared, that is, a thin alkali metal composite foil.
6. The method for preparing a thin alkali metal composite foil according to claim 5, characterized in that: The thickness t of the Na / Na-In composite foil is 1≤t≤35 μm.
7. Application of the thin alkali metal composite foil prepared by the preparation method according to any one of claims 3 to 6 in secondary battery electrodes, characterized in that: The secondary battery is a high specific energy sodium metal battery or a sodium ion battery.
8. The use of the thin alkali metal composite foil in a secondary battery electrode according to claim 7, characterized in that: The thin alkali metal composite foil serves as a negative electrode.
9. The use of the thin alkali metal composite foil in a secondary battery electrode according to claim 7, characterized in that: The thin alkali metal composite foil is used as a negative electrode sodium compensation material.
10. The use of the thin alkali metal composite foil in a secondary battery electrode according to claim 7, characterized in that: The positive electrode of the secondary battery is one of a sodium-containing transition metal oxide, a polyanion compound and a Prussian blue / white compound.
Citation Information
Patent Citations
Preparation method of lithium-gold-carbon nanotube composite foil material
CN110783547A
High-plasticity double-phase alkali metal alloy material, film processing method thereof and application of secondary battery
CN115663167A